Teacher Collegial Relationships and Children Learning Outcomes in a Government Early Childhood Centre in the St. George East Educational District of Trinidad and Tobago - Abbott, Shelly C. (My University, 2017)
This study investigated the extent to which teacher collegial relationships influenced curriculum delivery and learning outcomes at a government early childhood centre in Trinidad and Tobago. Data were collected through interviews with three teachers and one administrator/teacher of the centre. It was found that: 1) most of the teachers believed that the administrator was not very concerned about the state of collegial relations at the centre, 2) although the teachers seemed unaware of the impact of collegial relations at the centre, one of them acknowledged the possible impact of fractured relations on its climate, while another expressed the hope that teachers would put the centre first so that relations would improve, 3) curriculum delivery at the centre appeared to be somewhat impeded by frayed teacher collaboration and cooperation with respect to curriculum and lesson planning, role modelling, and the teachers’ ability to reflect on the power of the hidden curriculum, and 4) although there was no consensus that the children modelled the prevailing collegiality among their teachers, some of the teachers contended that the negativity among them was not transferred to the children.
Keywords: Case studies; Administrator attitudes; Teacher attitudes; Student teacher relationship; Early childhood care and education; Learning outcomes; Trinidad and Tobago